A feedback loop in PPARγ–adenosine A2A receptor signaling inhibits inflammation and attenuates lung damages in a mouse model of LPS-induced acute lung injury - He, Xie; Hu, Jian-Lin; Li, Jun; Zhao, Li; Zhang, Yan; Zeng, Yi-Jun; Dai, Shuang-Shuang; He, Feng-Tian (Cellular signalling, 2013)
Although peroxisome proliferator-activated receptor-γ (PPARγ) and adenosine A2A receptor (A2AR) are reported to be anti-inflammatory factors in acute lung injury (ALI), their internal link and synergic or antagonistic effect after activation are poorly understood. Here, we found that PPARγ and A2AR could upregulate the mRNA and protein expressions of each other in lung tissues of LPS-induced mouse ALI model and murine macrophages. Further investigation demonstrated that PPARγ upregulated A2AR expression by directly binding to a DR10 response element (−218 to −197) within A2AR gene promoter region. Instead of directly interacting with PPARγ, A2AR stimulated PPARγ expression via protein kinase A (PKA)–cAMP response element binding protein (CREB) signaling by provoking the binding of CREB to a cAMP responsive element (CRE)-like site in PPARγ gene promoter region. In addition, combination of PPARγ and A2AR agonists was found to exert obviously better effect on suppressing neutrophil infiltration and inflammatory cytokine expressions, attenuating lung edema, pathological changes and improving lung function of blood gas exchange than their single application. These findings reveal a novel functional positive feedback loop between PPARγ and A2AR signaling to potentialize their effect on inhibiting inflammation and attenuating lung damages in ALI. It suggests that targeting this PPARγ–A2AR signaling rather than PPARγ or A2AR alone may be a more attractive and efficient potential therapeutic strategy for ALI. [Display omitted] •A2AR is a novel target gene of PPARγ.•A2AR activation regulates expression and function of PPARγ via PKA-CREB signaling.•PPARγ and A2AR form a feedback loop to inhibit inflammation.•Combination of PPARγ and A2AR agonists exerts synergic protective effect in ALI.